STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA MADRASAH ALIYAH RUHUL ISLAM ANAK BANGSA BANDA ACEH - Khairuddin, Khairuddin (TABULARASA, 2014)
The purpose of this study was to determine the efforts made by the principal to improve the professional competence of teachers. This study used a qualitative approach with descriptive methods. Data was collected through interviews, observation and documentation. The subjects were school principals, vice principals and teachers. The results showed the principal has made a planning program to improve the professional competence of teachers, which gives permission to the teacher to go to college, training provides teaching materials in accordance with the applicable curriculum. Implementation of the program to improve the professional competence of teachers by requiring each subject teachers to make learning device according to the latest curriculum, adjusting the development of teachers handbook, make supervision schedule.